Монгол Улсын эдийн засгийн аюулгүй байдлыг бэхжүүлэхэд “гурав дахь хөршийн" үүрэг, холбогдол - Л, Оюунгэрэл (Journal of International Studies, 2007)
English title: The role and importance of the “third neighbor” in the strengthening of the economic security of Mongolia